Potensi Tindak Pidana Kriminal oleh Anak Remaja ditinjau dari Faktor Umur dan Pendidikan dengan Metode Multi Factor Evaluation Process (MFEP) - Limbong, Riswan; Siregar, Kristian (MEANS (Media Informasi Analisa dan Sistem), 2018)
According to statistics in 2013 there were 535 cases and in 2014 there were 723 cases, and based on the data there was an increase of Â± 1.35%. The cause of this crime is caused by many factors, but if the factors that cause this crime are known to be earlier by the parents (community), perhaps parents can educate their children and can reduce the number of juvenile perpetrators of physical criminal offenses. The physical crimes referred to in this study are: Robbery, Public order theft and murder. Multifactor Evaluation Process (MFEP) is a quantitative method that uses a "weighting system". In multifactorial decision making, decision makers are subjectively and intuitively weighing various factors that have an important influence on their alternative choices. For decisions that have a strategic influence, it is advisable to use a quantitative approach such as MFEP. In MFEP, all criteria are first, which are important factors in making consideration given appropriate weighting. The same steps are also taken for the alternatives to be chosen, which can then be evaluated in relation to these consideration factors. The MFEP method determines that the alternative with the highest value is the best solution based on the selected criteria.